Sustentación de los trabajos de titulación de la carrera de Ingeniería en Administración para Desastres y Gestión del Riesgo - Llivi Ruilova, Danny Vicente (2024)
The Dr. Gabriel Galarza López campus was the conducive setting for the support of the degree work of the Engineering in Disaster Administration and Risk Management career, of the Faculty of Health and Human Sciences of the UEB.